Hotelier: a Passion or a Profession? - Gita Subakti, Agung (Bina Nusantara University, 2013)
The history of hotels is intimately connected to that of civilizations. Or rather, it is a part of that history. Through years and time, many people are making their mark in the hotel industry by gaining the title as a Hotelier. Not just nationwide but they placed their footsteps throughout the world and became leading people in the Hospitality industry. The aim of this paper is to overview some of the people who had achieve the reputation as an Hotelier: globally recognized, set up their set of high quality standard, developing international brand and be able to sustain and succeed worldwide.